2018
DOI: 10.1177/0973217920902003
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Thyroid-Stimulating Hormone Level: Interpretation in Light of Antenatal and Perinatal Factors

Abstract: Objective: To study the influence of antenatal and perinatal factors on umbilical cord blood thyroid-stimulating hormone (CB TSH) levels. Design: Cross-sectional study. Setting: Private Medical College. Methods: CB TSH levels were measured in 1147 neonates using chemiluminescence immunoassay. The effect of antenatal and perinatal factors on CB TSH values was analyzed statistically. Results: The mean TSH value was 6.811 mIu/mL. A total of 44 neonates (3.83%) had a CB TSH value greater than 20 mIu/mL and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…In other words, mothers who gave birth once had higher levels of TSH in their fetal umbilical cord than mothers who gave birth twice or more. Similar to the findings of our study, several studies have reported an increase in the cord TSH level in first-born neonates compared to later-born ones [ 26 , 27 , 33 ]. Moreover, some studies have reported that first infants have higher TSH concentrations than subsequent ones [ 26 , 30 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In other words, mothers who gave birth once had higher levels of TSH in their fetal umbilical cord than mothers who gave birth twice or more. Similar to the findings of our study, several studies have reported an increase in the cord TSH level in first-born neonates compared to later-born ones [ 26 , 27 , 33 ]. Moreover, some studies have reported that first infants have higher TSH concentrations than subsequent ones [ 26 , 30 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the findings of our study, several studies have reported an increase in the cord TSH level in first-born neonates compared to later-born ones [ 26 , 27 , 33 ]. Moreover, some studies have reported that first infants have higher TSH concentrations than subsequent ones [ 26 , 30 , 34 ]. In contrast, one study from Belgium reported no differences in TSH levels according to birth order [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations